2007
DOI: 10.1302/0301-620x.89b4.18631
|View full text |Cite
|
Sign up to set email alerts
|

Endoprosthetic replacement of the distal femur for bone tumours

Abstract: We investigated whether improvements in design have altered the outcome for patients undergoing endoprosthetic replacement of the distal femur after resection of a tumour. Survival of the implant and 'servicing' procedures have been documented using a prospective database, review of the design of the implant and case records. In total, 335 patients underwent a distal femoral replacement, 162 having a fixed-hinge design and 173 a rotating-hinge. The median age of the patients was 24 years (interquartile range 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
243
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(266 citation statements)
references
References 48 publications
14
243
1
3
Order By: Relevance
“…Data from the Royal Orthopaedic Hospital published over a longer period of time with a greater number of patients demonstrate this point. The authors found an 83% implant survival at 5 years, and the risk of revision fell by 52% when rotating-hinge knee implants with hydroxyapatite collars were used in exchange for fixed-hinge knee implants with a smooth collar [19]. In that series, there were no patients with aseptic loosening in adult patients with cemented stems and hydroxyapatite collars at a mean followup of 12 years.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Data from the Royal Orthopaedic Hospital published over a longer period of time with a greater number of patients demonstrate this point. The authors found an 83% implant survival at 5 years, and the risk of revision fell by 52% when rotating-hinge knee implants with hydroxyapatite collars were used in exchange for fixed-hinge knee implants with a smooth collar [19]. In that series, there were no patients with aseptic loosening in adult patients with cemented stems and hydroxyapatite collars at a mean followup of 12 years.…”
Section: Discussionmentioning
confidence: 92%
“…Were the study to be started today, it would be possible to more carefully match CIS primary oncologic nonexpandable implants with the same CPS indications, for which a more robust patient population now exists. It is also important to note the reliability of Stanmore CIS implants has been well-documented, and furthermore, technical design advancement in these cemented limb salvage prostheses have been associated with improved implant longevity [19]. Data from the Royal Orthopaedic Hospital published over a longer period of time with a greater number of patients demonstrate this point.…”
Section: Discussionmentioning
confidence: 99%
“…Prosthetic reconstruction allows rapid restoration of mobility and weightbearing, but complications have been described in 25-92% of cases [2,3]. A 57% cumulative five-year survival for knee prostheses has been reported [4].…”
Section: Introductionmentioning
confidence: 99%
“…This type of reconstruction allows a functional reconstruction by preserving joint movement. There are, however, disadvantages, including infection, prosthesis loosening, the need to change prostheses in a growing child, a limitation to their function and lifestyle, and, perhaps the most significant disadvantage, limited durability, especially when performed in paediatric populations and in young adults [45,46]. To achieve an ideal reconstruction, the resected bone and joint should be replaced with an identical vascularised bone.…”
Section: Discussionmentioning
confidence: 99%